Pharmacist's legal protection as if for public officer - Kamila Piątkowska (Polish Pharmaceutical Society, 2024)
Work with patients carries increased risk of aggression and violence. Not only physicians, paramedics, nurses but also pharmacists are endangered. It was especially visible during the state of epidemy of SARS-CoV-2 in Poland when the pharmacist were facing physical violence in the pharmacies. In those situations the protection may be granting the public officer's status to medical professionals. Because of that all acts of aggression towards public officers' are punished much more severe and the penalties in the criminal code are intensified. Pharmacist are also considered as if they are public officers so they shall use the special protection and privileges. The aim of the work is to analyze legal provisions in the scope of the pharmacists' legal protection as if for public officers. It was carried out on the basis of initial parliamentary project, then on enacted as amendment to the Pharmacy Profession Act of 10 December 2020 and on the provisions from the polish criminal code that consider special legal status of public officer. It was explained what is exactly the public officer status within the unique aspects of polish legislation. In polish law system regulations that govern the public officer status result from many special laws and so it is in case of medical professions. What is more, the status only gives privileges and protection without burdening them with additional responsibility. There was also conducted a comparison of pharmacists legal status to legal provisions stating the status as if for public officer towards physicians, dentists, nurses and midwives. Those medical professions have been legally considered as public officers for many years now so it is possible to analyze functioning the provisions in practice. The new pharmacists' legal status as if for public officer constitutes a good start in polish legislation and it offers legal protection to the part of the polish pharmacists but it requires to be extended so there have been expressed postulates de lege ferenda.